The blood-brain barrier in neuroAIDS - (:unkn) unknown (BENTHAM SCIENCE PUBL LTD, 2006)
Nearly every aspect of blood-brain barrier (BBA) function is involved in or affected by HIV-1. The disruption of the BBB tends to be minimal and is not likely the mechanism by which infected immune cells and virus enter the brain. Instead, immune cells, virus and viral proteins likely activate brain endothelial cells and enable their own passage across the BBB by way of highly regulated processes such as diapedesis and adsorptive endocytosis. Viral proteins and cytokines can enter the CNS from the blood and provide a mechanism by which HIV-1 can affect CNS function independent of viral transport. Brain endothelial cells can also secrete neuroimmunoactive substances when stimulated by HIV-1, gp120, and Tat. Efflux systems such as p-glycoprotein transport anti-virals in the brain-to-blood direction, thus hampering effective accumulation of drug by the CNS. Overall, the BBB plays a major role in establishing and maintaining virus within the CNS and neuroAIDS.
Keywords: blood-brain barrier; transporter; virus; HIV-1; AIDS; cytokine; HUMAN IMMUNODEFICIENCY VIRUS-1; JUNCTION PROTEIN EXPRESSION; CENTRAL-NERVOUS-SYSTEM; NECROSIS-FACTOR-ALPHA; HORMONE ACTH ANALOG; IN-VITRO; P-GLYCOPROTEIN; ENDOTHELIAL-CELLS; INTRACEREBROVENTRICULAR INJECTION; CEREBROSPINAL-FLUID